On the margins of margins: the place of the feminine in São Paulo peripheral literature (PerCursos, 2021)
The essay analyzes the role of black writers from peripheral territories in marginal literature, based on the intertwining between literature, politics and insurgent movements in the contemporary São Paulo scene. Thereunto, the text seeks to contextualize the contribution of this important poetic collection produced by female literary circles in the dialogue between the biographical and the political. It is also a matter of reflecting on how these feminine poetic peripheral movements redefine identities and representations, through collectives of resistance articulated around slam, “saraus” and walking poetry. For this, in addition to the literature review, documentaries and video clips produced by women involved in the struggles of these movements are analyzed, considering the literary scenario divided into three moments: the marginal literature of the 2000s; the peripheral literature, from 2005 on; and the peripheral women's literature, produced since 2013, and its unfoldings. Finally, the essay focuses on the memoricide and the erasure of female literature in Brazil, especially the peripheral female literature in São Paulo, and the current strategies of denunciation and resistance that are produced by black writers from São Paulo, resignifying not only the public space, but also the political power of marginalized bodies and territories.
Keywords: peripheral literature.; feminism; racism; Slam; sarau